(untitled) (International Seven Journal of Multidisciplinary, 2024)
This paper presents the results of a Potentially Significant Teaching Unit (PSU), with the cross-cutting theme "Traffic Education", applied to a ninth grade class. This work derives from a qualitative study whose aim was to verify the potential of a PSU to promote meaningful learning of kinematics content. The materials and stages of the UEPS were based on the Meaningful Learning Theory. The assessment carried out during the UEPS was formative in nature, as the students were monitored as they carried out the tasks in the different stages. The data from the various assessment instruments was analyzed using descriptive statistics and Textual Discourse Analysis. The analysis showed that the aim of this work was achieved, as there was progress in understanding kinematics concepts and it helped to improve the students’ attitudes to deal more adequately with the complexity of the "Traffic" phenomenon. The study showed that the use of this cross-cutting theme produced relevant relationships for learning, contributing to new ways of teaching and learning science. This proposal therefore constitutes material that can be qualified as having the potential to develop meaningful learning.